Accuracy of Small Dense Low-density Lipoprotein-cholesterol Concentration Estimated via Sampson’s Equation in Healthy Subjects and Patients with Diabetes - Hirano, Tsutomu; Ito, Yasuki (Journal of Atherosclerosis and Thrombosis, 2023)
Aim: Sampson et al. proposed a method to calculate small dense low-density lipoprotein-cholesterol (sdLDL-C) concentrations using common lipid measurements, but its accuracy remains unresolved. We examined the difference between Sampson’s equation and direct measurement in patients with diabetes.Methods: sdLDL-C was measured directly by our established homogeneous assay and estimated by Sampson’s equation in patients with diabetes (n=1542) and healthy control subjects (n=673). Large-buoyant (lb)LDL-C was estimated using triglycerides and LDL-C, and sdLDL-C was obtained by subtracting lbLDL-C from LDL-C. The effect of fasting/nonfasting state or lipid-lowering drug therapy on sdLDL-C values was also examined in 30 and 43 patients with diabetes, respectively.Results: The coefficient of determination (R2) between calculated sdLDL-C and direct measurement was 0.73 and 0.61 for healthy controls and patients with diabetes, respectively. The R2 between calculated sdLDL-C and nonHDL-C or apolipoprotein B was 0.64 and 0.65, respectively. Calculated sdLDL-C was 4–5 mg/dl or 17%–18% higher than the direct measurement. The lower the plasma lipids, especially sdLDL-C, the greater the dissociation between the two methods. Sampson sdLDL-C was also found to give a positive bias when calculated for the nonfasting samples. Statins and pemafibrate significantly reduced sdLDL-C, but their therapeutic effect was underestimated by 5 mg/dl (24%) via Sampson’s equation.Conclusions: The correlation between Sampson’s equation and direct measurements of sdLDL-C was reduced in patients with diabetes. Furthermore, the correlations with nonHDL-C and apolipoprotein B were even higher than those with direct sdLDL-C. The accuracy of Sampson’s equation decreased with lower sdLDL-C concentrations and was also influenced by diet.